Definition of the Situation – a Misunderstood and Undervalued Concept. The Contribution of Literature - Perrotta, Rosalba (Italian Sociological Review, 2020)
Definition of the situation, the core concept of Symbolic interactionism, sometimes erroneously confused with Merton’s self-fulfilling prophecy, is often overlooked both in sociological theorization and in everyday life. Since human beings tend to believe in the existence of a solid, incontrovertible reality, they do not put themselves in the role of others to know their definitions of the situation; consequently, misunderstandings and suffering arise. Being often obscure, difficult to grasp and remote from the men and women it studies, sociological theory that could help to improve social life often remains in textbooks. As social sciences and good literature have the same object of interest - human beings and their relationships - a better formulation and better understanding of sociological theorizations could be obtained by linking them to novels, short stories and plays. Narratives could clarify sociological concepts and highlight their potentialities. I have focused here on two episodes, one taken from Mark Twain’s The Adventures of Tom Sawyer, the other from Elizabeth von Arnim’s The Pastor’s Wife, that let us see how the same object can be defined in opposite ways. Subsequently, I have highlighted how the contributions of Proust and Pirandello, two authors who look at reality with a symbolic interactionist gaze, could help in better understanding the dramatic power and the fragility of the definitions that give sense to human behavior and human existence.